2021
DOI: 10.3389/fcvm.2021.668503
|View full text |Cite
|
Sign up to set email alerts
|

Computed Tomography Derived Coronary Triangulated Orifice Area—Deduction of a New Parameter for Follow-up After Surgical Correction of Anomalous Aortic Origin of Coronary Arteries and Call for Validation

Abstract: Introduction: Anomalous aortic origin of a coronary artery (AAOCA) from the opposite sinus of Valsalva is a rare congenital abnormality. Computed tomography angiography (CTA) is primarily used as a diagnostic tool to evaluate the anatomy and identify potentially malignant AAOCA variants. Limited data is available on the role of CTA during postoperative follow-up. We aimed to develop an objective CTA derived parameter for diagnostic evaluation and follow-up after surgical correction of AAOCA and correlate the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Specifically, myocardial ischemia can be attributed to fixed extent component (e.g. slit-like ostium), proximal narrowing, acute take-off angle and intramural course with an elliptic vessel shape [ 16 19 ], as well as dynamic component (e.g., lateral compression) that are accentuated during exercise [ 12 , 20 22 ]. In this study, coronary stenosis was mostly found in the middle or distal segments of coronary arteries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, myocardial ischemia can be attributed to fixed extent component (e.g. slit-like ostium), proximal narrowing, acute take-off angle and intramural course with an elliptic vessel shape [ 16 19 ], as well as dynamic component (e.g., lateral compression) that are accentuated during exercise [ 12 , 20 22 ]. In this study, coronary stenosis was mostly found in the middle or distal segments of coronary arteries.…”
Section: Discussionmentioning
confidence: 99%
“…The various pathological aspects associated with malignant AAOCA collectively contribute to a significantly reduced functional ostial area in the anomalous coronary artery, leading to ischemia and potentially fatal arrhythmias [ 16 ]. The potential mechanisms underlying AAOCA-induced ischemia may be resulted from the origin, the anatomy of the origin [ 16 19 ], the angulation, and the dynamic compression [ 12 , 20 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Coronary artery motion during the CTA produces temporal and spatial blurring that can effectively result in a lower spatial resolution than intended. 18 Thus, it would be advisable to use a slice thickness of 0.5 mm on CTA in all cases for the evaluation of the ILS to obtain the most reliable results. In the current study, CTAs were performed in the different referring hospitals following local protocols; therefore, not all scans included in this study were performed according to the same scanning protocol.…”
Section: Discussionmentioning
confidence: 99%
“…Images were rotated to a view perpendicular to the horizontal plane of the aortic valve annulus according to previously described methods. 18 In this view, the distance between the aortic lumen and coronary artery lumen [further referred to as ‘interluminal space’ (ILS)] was measured at consecutive 2 mm intervals along the length of the intramural segment that was measured peroperatively by the surgeon. The surgical measurements were used as the reference to define the length of the intramural segment ( Figure 1B ).…”
Section: Methodsmentioning
confidence: 99%